Finding Nemo. (Pasig City : Viva Video, 2003)
From the Academy Award - winning* creators of Toy Story and Monsters, Inc. it's time to dive into FINDING NEMO - a hilarious adventure where you'll meet colorful characters that take you into the breathtaking under world of Australia's Great Barrier Reef. Nemo, an adventurous young Clownfish, is unexpectedly taken to a dentist's office aquarium. It's up to Marlin, his worrisome father, and Dory, a friendly but forgetful regal blue tang fish, to make the epic journey to bring Nemo home. Their adventure leads them face-to-face with vegetarian sharks, surfer dude turtles, hypnotic jellyfish, hungry seagulls and more. Marlin discovers a bravery he never knew, but will he be able to find his son? FINDING NEMO's breakthrough computer animation takes you into a whole new world with this undersea adventure about family, courage, and challenges. Swinning with laughs and overflowing with emotion - you'll find yourself watching FINDING NEMO over and over again!